2020
DOI: 10.15421/2020_298
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perennial legumes on the productivity of meadow phytocenoses

Abstract: We investigated the effectiveness of soil liming during grass sowing and application of inoculation of perennial legume grass seeds with nitrogen-fixing and phosphate-mobilizing preparations. Methods. Field studies were conducted during 2016-2020 in the National Scientific Center "Institute of Farming of the National Academy of Agrarian Sciences of Ukraine" (northern part of the Forest-steppe of Ukraine, Chabany settlement, Kiev-Svyatoshinsky district of Kyiv region). Area of the sowing plot was 30 m2, control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 3 publications
(3 reference statements)
1
9
0
Order By: Relevance
“…According to the data listed in Table 2 on the background of all fertilisers, a higher ratio of calcium to phosphorus Ca:P (in the range of 1.33-1.51) and a lower ratio of potassium to the sum of calcium and magnesium (K:(Ca+Mg)) (in the range of 3.04-3.58) were in the dry mass of alfalfa and alfalfa-cereal mixtures, which, respectively, is 0.11-0.26 units more and 0.83-2.08 units less than in dry feed biomass cereal stand. Similar patterns regarding the effect of nitrogen symbiotic fixation on changes in the ratio of these macroelements in the dry mass of feed were observed by other researchers (Karbivska 2019; Demidas & Galushko, 2020; Kurhak et al, 2020).…”
Section: Source: Compiled By the Authorssupporting
confidence: 88%
See 2 more Smart Citations
“…According to the data listed in Table 2 on the background of all fertilisers, a higher ratio of calcium to phosphorus Ca:P (in the range of 1.33-1.51) and a lower ratio of potassium to the sum of calcium and magnesium (K:(Ca+Mg)) (in the range of 3.04-3.58) were in the dry mass of alfalfa and alfalfa-cereal mixtures, which, respectively, is 0.11-0.26 units more and 0.83-2.08 units less than in dry feed biomass cereal stand. Similar patterns regarding the effect of nitrogen symbiotic fixation on changes in the ratio of these macroelements in the dry mass of feed were observed by other researchers (Karbivska 2019; Demidas & Galushko, 2020; Kurhak et al, 2020).…”
Section: Source: Compiled By the Authorssupporting
confidence: 88%
“…In the studies (Kotyash et al, 2019; Demidas & Galushko, 2020; Martsinko et al, 2021), as in this one, it was shown that under the action of symbiotic nitrogen in alfalfa and alfalfa-cereal stands, compared with cereals among mineral elements, to the greatest extent increased the content of calcium and magnesium in the dry mass of feed (respectively, to 0.86-1.07% and to 0.21-0.35%), and the content of potassium decreased. Kurhak et al (2020) in their study identified that when applying high doses of nitrogen fertilisers to a perennial cereal stand, the nitrate content increases in the aboveground biomass of cereals in an amount that may exceed the maximum permissible concentration. When applying moderate doses of nitrogen fertilisers, as a rule, despite the fact that the accumulation of nitrates in the dry mass of feed increases, it does not exceed the MPC and is not harmful to animals, which confirms this and similar studies.…”
Section: Table 4 Content Of Trace Elements and Heavy Metals In The Dr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the experimental data presented in the studies (Demidas & Galushko, 2020;Kurhak et al, 2020) concerns changes in the microelement composition of feed from perennial cereals under the influence of nitrogen and mineral fertilisers. In particular, it was identified that under its influence, the copper content in the feed biomass of perennial cereals depends on its presence in the soil.…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%
“…During studies in the northern part of the foreststeppe of Ukraine, it was found that symbiotic nitrogen accumulates the most in alfalfa plants (1.91-2.66 centner/ha), and the least -in meadow clover plants (Kurhak et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%